P197 The endoscopy safety attitudes questionnaire (Endo-SAQ): validation and results. (19th June 2022) - Ravindran, Srivathsan; Matharoo, Manmeet; Healey, Chris; Marshall, Sarah; Bassett, Paul; Coleman, Mark; Ashrafian, Hutan; Darzi, Ara; Thomas-Gibson, Siwan
Abstract : Introduction: Safety culture is fundamental in healthcare. Safety attitudes, a surrogate for safety culture, have been linked to patient outcomes. We report the results of a national survey of safety attitudes in endoscopy and validation of the Endo-SAQ (Endoscopy Safety Attitudes Questionnaire). Methods: The Endo-SAQ consists of 35 Likert-scale questions across 6 domains: teamwork (working with others), safety climate (general patient safety attitudes), job satisfaction, stress recognition (ability to understand impact of stress on role), perceptions of management and working conditions. The survey was disseminated online to endoscopy staff in UK and Ireland. Outcomes measures were domain scores (calculated from the mean question rating within each domain; maximum score = 100) and percentage of positive responses (PPR) per domain. Scores above 75 reflect positive safety attitudes in that domain. Descriptive and comparative analyses were performed including Friedman's test to assess differences across domain scores with post-hoc tests using Wilcoxon's signed-rank test. Binary logistic regression, using a forward selection method, was used to identify predictors of positive scores. Validity and reliability of Endo-SAQ were assessed through confirmatory factor analysis, Cronbach's alpha and composite reliability measures. Results: 453 participants completed the Endo-SAQ. There were positive attitudes in teamwork, safety climate, job satisfaction and working conditions domains (scores > 75; Figure 1 ). Endoscopists had higher scores in stress recognition (p = 0.02) and working conditions domains (p = 0.03) than nursing staff. Joint Advisory Group on Gastrointestinal endoscopy (JAG) accreditation was a positive predictor in safety climate (OR 1.92, p = 0.02) and job satisfaction (OR 2.09, p = 0.004) domains. Female gender was a negative predictor in teamwork (OR 0.59, p = 0.03), safety climate (OR 0.52, p = 0.01), job satisfaction (OR 0.63, p = 0.047) and working conditions (OR 0.35, p < 0.001) domains. All tests of model fit met accepted thresholds. Cronbach's alpha was > 0.8 and composite reliability > 0.7 for all domains. These results indicate Endo-SAQ met construct validity and reliability thresholds. Conclusions: Endoscopy staff had largely positive safety attitudes but there were significant differences across domains and staff subtypes. There is evidence to support the validity and reliability of Endo-SAQ.